Conducting the Needs Assessment #10: The Delphi Technique - Laura A. Sanagorski Warner; Amy Harder (EDIS, 2020)
Previous publications in the Conducting the Needs Assessment series outlined why, how, and when Extension educators and other service providers should use needs assessments in their programs. The four preceding publications in the series provide Extension educators and other service providers with specific techniques that can be used in needs assessments, and this new 5-page publication provides an overview of using the Delphi technique to conduct a needs assessment. Written by Laura Warner and Amy Harder, and published by the UF/IFAS Department of Agricultural Education and Communication.